2020
DOI: 10.1155/2020/8953453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacterial Translocation and Autophagy on Acute Lung Injury Induced by Severe Acute Pancreatitis

Abstract: Aim. To reveal the role of bacterial translocation (BT) and autophagy in severe acute pancreatitis-induced acute lung injury (SAP-ALI). Methods. Rats were separated into a control (sham-operation) group (n=10) and a SAP group (n=30). Sodium taurocholate (5%) was retrogradely injected into the cholangiopancreatic duct to induce SAP-ALI in rats. Then, 16S rDNA sequencing was used to detect bacterial translocation (BT). Hematoxylin eosin staining (HE) was used to detect morphological changes to the pancreas, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Consequently, clarification of the process of impaired autophagy early in AP could provide a new target for clinical exploration for novel AP drugs. Oxidative stress is also increased due to bacterial translocation, which further aggravates AP-associated lung injury, this process may be related to decreased autophagy level (63). The AP models of IL-22 transgenic mice and IL-22 recombinant adenovirus mice induced by caerulein confirmed that IL-22 can prevent the formation of autophagosomes through the Beclin-1 pathway, thereby reducing the severity of AP (64).…”
Section: Impaired Autophagymentioning
confidence: 86%
“…Consequently, clarification of the process of impaired autophagy early in AP could provide a new target for clinical exploration for novel AP drugs. Oxidative stress is also increased due to bacterial translocation, which further aggravates AP-associated lung injury, this process may be related to decreased autophagy level (63). The AP models of IL-22 transgenic mice and IL-22 recombinant adenovirus mice induced by caerulein confirmed that IL-22 can prevent the formation of autophagosomes through the Beclin-1 pathway, thereby reducing the severity of AP (64).…”
Section: Impaired Autophagymentioning
confidence: 86%
“…This process also enhances the secretion of inflammatory molecules including IL-6 and TNF-α. 192 , 193 In addition, there is a positive correlation between the abundance of Enterobacter, Enterococcus and the expression of inflammatory factors (IL-6 and TNF-α), suggesting the role of pathogenic bacteria in accelerating the inflammatory responses under SAP-ALI. 188 The relative abundance of Bacteroides and Prevotella , which are important SCFAs-producing bacteria, decreased during SAP, resulting in the reduction of propionate, butyrate and valerate.…”
Section: Gut Microbiota and Intestinal Mucosal Immune Barriermentioning
confidence: 99%
“…Reduced autophagy in severe AP impairs tight and gap junctions and reduces the function of goblet and Paneth cells, leading to increased bacterial translocation and extra-pancreatic serious manifestations [370,378,379]. The increase in oxidative stress associated with the increased bacterial translocation will aggravate AP-associated lung injury and was attributed to decreased autophagy levels [380]. However, the opposite has also been reported, as excessive autophagy may also be connected to lung injury.…”
Section: Autophagy In Pancreatitismentioning
confidence: 99%